Uso de la higuereta (Ricinus communis, L.) en el control de roedores - Suarez, N.=700 1 Mora, P.P.; Rodriguez, M.E.
(Es, En)
Ilus., 15 ref.
Keywords: RATTUS; MUS; PLAGAS DE ANIMALES; CONTROL DE ROEDORES; CONTROL BIOLOGICO; RICINUS COMMUNIS; CUBA; RATTUS NORVEGICUS; MUS MUSCULUS